FURTHER GENERALIZATIONS OF MINKOWSKI TYPE INEQUALITIES WITH EXTENDED MITTAG-LEFFLER FUNCTION - Andrić, Maja; Farid, Ghulam; Pečarić, Josip; Usama Siddique, Muhammad (Matematichki Bilten, 2020)
The paper presents generalizations of Minkowski type integral inequalities for a generalized fractional integral operator containing an extended Mittag-Leffler function in the kernel.